Brain Functional Basis of Subjective Well-being During Negative Facial Emotion Processing Task-Based fMRI. (15th December 2019) - Ren, Zhiting; Shi, Liang; Wei, Dongtao; Qiu, Jiang
Highlights: SWB was positively correlated with right posterior cingulate cortex. SWB was positively associated with the FC between FPN and SMN. SWB was negatively associated with the FC within DMN. SWB was negatively associated with the FC within low-level perceptual networks. Abstract: Subjective well-being (SWB) is the eternal pursuit of all mankind. Individual differences in SWB may reflect the way of emotional processing. Neuroimaging studies have partly examined the neural mechanism of the individual differences in SWB using resting-state functional magnetic resonance imaging (rs-fMRI). However, few studies have investigated the relationship between the individual differences in SWB and brain functional connectivity during facial emotion processing task. Here, we applied negative facial emotion processing task-based fMRI to explore the brain functional basis of the individual differences in SWB. Results showed that SWB is positively correlated with the activation of right posterior cingulate cortex, left interior temporal gyrus and left angular gyrus for the comparison of negative stimulus and neutral stimulus, revealing that happy individuals may be more proactive to use attention transfer and behavioral inhibition strategies to decrease negative experiences during negative emotional processing. In addition, high SWB is associated with strong functional connectivity between high-level cognitive networks (e.g., frontal-parietal network) and low-level perceptual networks (e.g., sensorimotor network), and weak functional connectivity within default mode network and within low-level perceptual networks, indicating that the self-reflection, emotional regulation and cognitive control during negative facial emotion processing underlies the individual differences in SWB. These findings provide a novel insight to characterize the brain functional basis of the individual differences in SWB.